Controlled Release of Biological Control Agents for Preventing Aflatoxin Contamination from Starch–Alginate Beads - Jiachang Feng; Jianpeng Dou; Zidan Wu; Dongxue Yin; Wenfu Wu (Molecules, 2019)
For the wise use of fungal biocontrol and metalaxyl fungicide, starch–alginate-based formulations have been developed by encapsulating metalaxyl and non-toxigenic Aspergillus flavus spores simultaneously in the form of microspheres using calcium chloride as a cross-linking agent. The formulations were characterized by Fourier transform infrared spectroscopy (FTIR), a scanning electron micrograph (SEM), and thermogravimetry (TGA). Formulation characteristics, including the bead size, entrapment efficiency, swelling ratio of the beads, and rheological properties, were analyzed. The release behavior of beads with different formulations was evaluated. The addition of kaolin and rice husk powder in starch–alginate beads retarded the release profile of spores and metalaxyl. The release of the active ingredient from starch–alginate–kaolin beads and starch–alginate–rice husk powder beads occurred in both a controlled and sustained manner. Additionally, the release rate decreased with the increase of kaolin or rice husk powder content. The beads added with kaolin were slower than the release of rice husk powder. In comparison, spores released slower and lasted longer than metalaxyl. The starch–alginate–kaolin formulations could be used as controlled release material in the field of biocontrol and reduce the harm of fungicides to the environment.